Effects of L-carnitine and Pentoxifylline on the Activity of Lactate Dehydrogenase C4 isozyme and Motility of Testicular Spermatozoa in Mice - E Aliabadi; F Karimi; M Rasti; M Akmali; T Esmaeilpour (JRI, 2013)
Background: Extracted sperm from the testis have poor motility. Moreover, their motility changes during their journey through epidydimis. Meanwhile, they face high concentration of L-carnitin. In addition, lactate dehydrogenase C4 (LDH-C4) gene disorders has been shown to cause impaired sperm motility, leading to infertility in male mice. The aim of this study was to evaluate sperm motility and LDH-C4 ezyme activity upon L-carnitine (LC) and Pentoxifylline (PTX) administrations in mice. Methods: We extracted testicular sperm of 48 mice and divided them into three equal parts. One part was incubated with Ham's F10 medium (control), the other parts were treated with Ham's F10 containing LC and PTX with a final concentration of 1.76 mM, for 30 min at room temperature. Sperm motility was assessed according to the World Health Organization (WHO) criteria. Sperm LDH-C4 enzyme activity was measured by spectrophotometery method. Statistical analyses were performed using ANOVA and Fisher's LSD test, and a p-value less than 0.05 was considered as a statistically significant difference. Results: Sperm motility increased after 30 min of incubation in LC- and PTX-treated group (p<0.001). LC and PTX administrations showed a significant increase in the LDHC4 enzyme activity of sperm compared to that of the controls after 30 min (P=0.04 and 0.01, respectively). Conclusion: The effects of LC and PTX on motility of sperm can be explained by an increase in LDH-C4 enzyme activity that may influence male fertility status. We suggest that LC as a non-toxic antioxidant is more suitable for use in assisted reproductive technique protocols than PTX.
Keywords: L-carnitine, LDH-C4, Male infertility, Pentoxifylline, Testicular sperm